High Rate of Asymptomatic Myocardial Ischemia in HIV Infected Population in Bobo-Dioulasso in Burkina Faso - Tougoouma S. J. B.; Zoungrana J.; Yameogo A. A.; Yameogo N. V.; Diallo I.; Hema A.; Hien H.; Some A. S.; Traore T. I.; Millogo G. R. C.; Kologo K. J.; Sawadogo S.; et al. (Journal of Clinical Research In HIV AIDS And Prevention, 2016)
Introduction The cardiovascular complications have became the 3rd cause of death and the 4th reason for hospitalization of the patients infected by the HIV. The objective of this work was to determine the frequency of asymptomatic myocardial ischemia among patients infected by the HIV receiving antiretroviral therapy. Patients and Methods It was a descriptive cross-sectional study which was conducted in November 2015. The patients infected by HIV1 receiving antiretroviral treatment, with asymptomatic myocardial ischemia were included in the study and they were followed up in the HIV clinic of the in Infectious diseases service of the University Hospital Souro Sanou of Bobo-Dioulasso(CHUSS).. The includes patients benefited from a collection of cardiovascular risk factors, and of two measurements of the blood pressure in a sitting position after 10 minutes of rest and an electrocardiogram 12 derivations after rest. Results A total sample of 123 patients infected by HIV1 was selected, with a median age of 42 years (IQR: 36-50). It was composed of 79% of female. The cardiovascular risk factors found were distributed as follows: HTA (31.7%), obesity (33%), dyslipidemia (10.57%), active smoking (0.8%), diabetes (0.8%). All the known hypertensive cases (5.7%) were insufficiently treated. The median duration of exposure to the antiretroviral therapy was 5.3 years (IIQ: 3-7.7). The disorders of the repolarization were observed in 26 cases (21.13%). They were divided into under epicardic ischemia in 20 cases (16.26%), under endocardic lesion in 2 cases (1.63%) and after-effect of necrosis in 4 cases (3.25%). The Left ventricular hypertrophywas observed in 12 cases (9.76%) and all of them were hypertensive patients. QTc was lengthened among 7 patients (5.69%) independently of the class of antiretroviral therapy administrated. Conclusion In this study about patients infected by HIV1, it emerges that asymptomatic myocardial ischemia is frequent. It would be advisable to reinforce its tracking by using more powerful tests of ischemia, in order to better specify its gravity in this population with an increased cardiovascular risk.
Keywords: Asymptomatic myocardial ischemia